The venus theory the science of global warming - Toiviainen, Pasi; Hentula, Jarkko; Talent House (Firm) (San Francisco, CA : The Video Project, 2004)
The documentary interviews the world's leading climate researchers and sketches, in the light of the latest scientific findings, an overview of the greenhouse effect. The story begins in the 1950s, with the path-breaking carbon dioxide measurements by Professor Charles Keeling from the Scripps Institution of Oceanography
Title from title screen
Director of photography, Jyri Hakala ; editor Kimmo Kohtamäki
DVD format
Keywords: Greenhouse effect, Atmospheric; Global warming; Climatic changes; Television programs -- Finland